Cytotoxicity and DNA protective effects of the Terfezia and Picoa species from the eastern region of Turkey - Akyuz, Mehmet; Karagoz, Isik Didem; Inci, Sule; Kilic, Ibrahim Halil; Kirbag, Sevda; Simitcioglu, Basak (Istanbul Univ, Fac Pharmacy, 2021)
Background and Alms: This study aims to investigate the cytotoxicity and DNA protective effects of semi-arid, arid, or desert truffles such as the Terfezia and Picoa species. Methods: The DNA protective effects of the Terfezia and Picoa species was evaluated using plasmid pBR322 DNA treated with UV and H2O2. The cytotoxic effects of waterand methanol extracts of the Terfezia and Picoa species on H1299 and HUVEC cells were evaluated using the MTT assay. Results: Higher concentrations of T. otbiensis and P. lefebvrei extracts have demonstrated a DNA protective effect. The water extract of P. juniperi only at a 40 mg/mL concentration demonstrated a DNA-protective effect, whereas T. boudieri extract did not show any DNA-protective effect at all concentrations tested. H1299 cells showed more sensitivity to the water extract of T. otbiensis (4.66%), P. juniperi (12.04%), P. lefebvrei (21.93%), and the methanol extract of T. boudieri (20.93%). In general, the water and methanol extracts of the Terfezia and Picoa species demonstrated the least cytotoxic effects on HUVEC cells, except for the water extract of P. juniperi (38.46%). Conclusions: In conclusion, results obtained from this study show that the Terfezia and Picoa truffle species have potential DNA protective and cancer prevention properties.
Keywords: arid-semi arid truffle; DNA protective activity; cytotoxicity effect; mushroom; Terfezia; Picoa